1997
DOI: 10.1091/mbc.8.10.1889
|View full text |Cite
|
Sign up to set email alerts
|

14–3-3 Inhibits theDictyosteliumMyosin II Heavy-Chain-specific Protein Kinase C Activity by a Direct Interaction: Identification of the 14–3-3 Binding Domain

Abstract: Myosin II heavy chain (MHC) specific protein kinase C (MHC-PKC), isolated from Dictyostelium discoideum, regulates myosin II assembly and localization in response to the chemoattractant cyclic AMP. Immunoprecipitation of MHC-PKC revealed that it resides as a complex with several proteins. We show herein that one of these proteins is a homologue of the 14 -3-3 protein (Dd14 -3-3). This protein has recently been implicated in the regulation of intracellular signaling pathways via its interaction with several sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 44 publications
2
23
0
Order By: Relevance
“…It is therefore likely that the downstream effects of PKC⑀ are mediated by the C1 domains. These structures have in several studies been shown to exert different biological effects (Lehel et al, 1995;Pawelczyk et al, 1998;Kiss et al, 1999;Aroca et al, 2000) and to interact with other proteins (Matto-Yelin et al, 1997;Yao et al, 1997;Pawelczyk et al, 1998;Hausser et al, 1999;Johannes et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore likely that the downstream effects of PKC⑀ are mediated by the C1 domains. These structures have in several studies been shown to exert different biological effects (Lehel et al, 1995;Pawelczyk et al, 1998;Kiss et al, 1999;Aroca et al, 2000) and to interact with other proteins (Matto-Yelin et al, 1997;Yao et al, 1997;Pawelczyk et al, 1998;Hausser et al, 1999;Johannes et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings do not exclude the possibility that Myo2 is phosphorylated at other sites by protein kinases other than those in the septation pathway. In Dictyostelium, myosin II is phosphorylated by a myosin heavy chain specific protein kinase C (Matto-Yelin et al, 1997) and the fission yeast protein kinase C homolog Pck2 localizes to the division site at cytokinesis (Sayers et al, 2000). Myo2 is not regulated by phosphorylation of conserved sites in its essential light chain Cdc4 and the regulatory light chain Rlc1 lacks the serine at amino acid position 19 that is associated with the regulation of Myo2 function in nonmuscle cells (Bresnick, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Many investigators have reported that 14-3-3s act as potential regulators of PKC, which is controlled by the interactions between them [10][11][12][13]. However, the effects of 14-3-3 on PKC have been controversial, showing conflicting results of inhibition or activation [5,9,13], and the biological significance of this event remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…However, the effects of 14-3-3 on PKC have been controversial, showing conflicting results of inhibition or activation [5,9,13], and the biological significance of this event remains unclear. In the present study, we sequentially confirmed decreased 14-3-3 ζ levels, up-regulated PKC and less interaction between the two in the diabetic retina.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation